2019
DOI: 10.1111/ele.13407
|View full text |Cite
|
Sign up to set email alerts
|

Evenness effects mask richness effects on ecosystem functioning at macro‐scales in lakes

Abstract: Biodiversity–ecosystem functioning (BEF) theory has largely focused on species richness, although studies have demonstrated that evenness may have stronger effects. While theory and numerous small‐scale studies support positive BEF relationships, regional studies have documented negative effects of evenness on ecosystem functioning. We analysed a lake dataset spanning the continental US to evaluate whether strong evenness effects are common at broad spatial scales and if BEF relationships are similar across di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 55 publications
5
7
0
Order By: Relevance
“…Again, this result concurs with previous findings documenting a negative relationship between phytoplankton evenness and the production of zooplankton biomass per unit of phytoplankton biomass in lakes (Filstrup et al, 2014). However, it differs from Filstrup et al (2019) who found a nonsignificant role of phytoplankton richness in driving zooplankton resource use efficiency in lakes.…”
Section: Phytoplankton and Zooplankton Resource-use Efficiencysupporting
confidence: 91%
See 3 more Smart Citations
“…Again, this result concurs with previous findings documenting a negative relationship between phytoplankton evenness and the production of zooplankton biomass per unit of phytoplankton biomass in lakes (Filstrup et al, 2014). However, it differs from Filstrup et al (2019) who found a nonsignificant role of phytoplankton richness in driving zooplankton resource use efficiency in lakes.…”
Section: Phytoplankton and Zooplankton Resource-use Efficiencysupporting
confidence: 91%
“…A simultaneous detection of a positive and negative effect of richness and evenness, respectively, on ecosystem function as the one observed here, was shown also by others either in fresh (Filstrup et al, 2019) or marine (Napoleón et al, 2014) waters. However, there are contrasting results on the relative contribution of the two effects, that is, the differences between the strength of the relationships.…”
Section: Phytoplankton and Zooplankton Resource-use Efficiencysupporting
confidence: 88%
See 2 more Smart Citations
“…RUE is directly affected by climate, abiotic and biotic attributes in terrestrial and aquatic ecosystems (Hodapp et al 2019), such as warming (Bestion et al 2018), nutrient (Verbeek et al 2018), and biodiversity (Gagic et al 2015). Phytoplankton diversity is frequently revealed to be an important driver of phytoplankton RUE in artificial or natural communities (Cardinale et al 2006(Cardinale et al , 2012, as it can enhance the available RUE at higher levels of species richness or at lower levels of evenness through complementary or selecting effects (Filstrup et al 2019). However, the direction and strength of the dependency of RUE on phytoplankton diversity remains largely unquantified across spatial and temporal scales, especially in freshwater ecosystems (Olli et al 2014;Hodapp et al 2019).…”
mentioning
confidence: 99%